2004
DOI: 10.1055/s-2004-813321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melatonin on Acute Necrotizing Pancreatitis in Rats

Abstract: The aim of this study was to investigate the influence of melatonin on acute necrotizing pancreatitis (ANP) induced by glycodeoxycholic acid in rats. The induction of ANP resulted in significant increases in mortality rate, pancreatic necrosis and increased serum activity of amylase, alanine aspartate transferase (ALT), interleukin 6 (IL-6), lactate dehydrogenase (LDH) in bronchoalveolar lavage (BAL) fluid, serum concentration of urea, tissue activity of myeloperoxidase (MPO) and malondialdehyde (MDA) in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 19 publications
(35 reference statements)
2
34
0
Order By: Relevance
“…Melo et al [28] stated that serum AM and LP levels are important diagnostic markers for AP. They usually rise within 4-8 h of the initial attack, peaks at 24 h, and returns to normal over the 72 h. On the contrary, Alhan et al [2] found that Mel did not change the serum activity of AM and aspartate transferase. In this study, TNF-a did not increase significantly during the course of AP.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Melo et al [28] stated that serum AM and LP levels are important diagnostic markers for AP. They usually rise within 4-8 h of the initial attack, peaks at 24 h, and returns to normal over the 72 h. On the contrary, Alhan et al [2] found that Mel did not change the serum activity of AM and aspartate transferase. In this study, TNF-a did not increase significantly during the course of AP.…”
Section: Discussionmentioning
confidence: 93%
“…They found that high endogenous Mel serum levels in the first 24 h after the onset of AP played a protective role in the course of the disease in humans. Moreover, pinealectomy significantly aggravated the histological manifestations of AP [23] on the other hand, Alhan et al [2] assumed that Mel has a limited value on the course of AP as it did not alter pancreatic damage or its mortality rate in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic necrosis has been defined as loss of acinar cells followed by the development of fibrosis (Hyun and Lee 2014). This is most likely the primary cause of the significant deterioration of pancreas function and microcirculation disorders (Banks et al 1996;Alhan et al 2001;Sugimoto et al 2004). In our study, the efficacy of CAR treatment in reducing fibrosis and improving regeneration was firstly determined in AP rat pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Alhan et al showed an increased apoptotic index (AI) in experimental acute pancreatitis in rats, probably due to oxidative stress-related activation of caspase pathways (9). They did not find any effect of p53 inactivation therapy during the course of pancreatitis, which suggested that p53 does not play a role in the apoptotic mechanism in acute experimental pancreatitis design (9).…”
Section: Introductionmentioning
confidence: 96%